From Products to Services A framework for Developing a Servitization Business Model in the Textile Industry - Mahdavi, Rajan; Fogelström, Anton (My University, 2023)
Companies can become more sustainable by adopting a servitization based business model which is circular rather than linear. When ownership of the product remains with the producer, incentives to create a high-quality product with a long lifetime is generated, hence the product can be rented out several times and therefore become a part of the circular economy. The purpose of this thesis is to evaluate different business models of rental based companies which are and are not operating to date. This will be done through the business model canvas framework in order to identify specific inputs which have positive and negative impacts. One conclusion drawn from the research is that the combination of narrow customer segments and monthly subscription-based revenue streams are not a successful practice when it comes to the B2C segment. Another interesting finding is that even though the unsuccessful companies are no longer in operation, their social media platforms have been constantly growing, thus showing an increased demand for different types of rental services within the textile industry. To come to these findings and conclusions this thesis has used a research methodology mainly based on qualitative research in order to collect data and information to evaluate and assess different approaches used by companies in the servitization business. The qualitative research conducted was based on semi-structured interviews in order to understand the current state of the market, demand and feasibility of a servitization/rental business model according to the business model canvas.
Keywords: Circularity; Servitization; Textile; Sourcing; Business Model Canvas